2012
DOI: 10.4251/wjgo.v4.i7.181
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin induced disseminated intravascular coagulation: A case report and review of literature

Abstract: Oxaliplatin in combination with a fluoropyrimide is a treatment option for colorectal cancer patients in the adjuvant and metastatic settings. Very few hematological emergencies have been reported associated with Oxaliplatin. These include autoimmune hemolytic anemia, thrombocytopenia and pancytopenia. We present a case report of a patient who developed hematuria and disseminated intravascular coagulation while receiving the second cycle of FOLFOX and bevacizumab for metastatic colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
11
0
2
Order By: Relevance
“…In 2012, Kurian et al reported a case of oxaliplatin-induced transient DIC in a 66-year-old patient with mildly increased prothrombin time/PTT, decreased fibrinogen, and normal hematocrit and platelet levels. 24 To our knowledge, our report is the second case of DIC and the first case of DIC and independent immune hemolytic anemia, possibly Evans syndrome, that are likely related to oxaliplatin infusion. Bevacizumab cannot be completely ruled out as the cause of DIC in this patient, although there is far less evidence that bevacizumab can induce the hematological events described in this case report, the only evidence being a case series of renal TMA associated with vascular endothelial growth factor inhibition.…”
Section: Discussionmentioning
confidence: 87%
“…In 2012, Kurian et al reported a case of oxaliplatin-induced transient DIC in a 66-year-old patient with mildly increased prothrombin time/PTT, decreased fibrinogen, and normal hematocrit and platelet levels. 24 To our knowledge, our report is the second case of DIC and the first case of DIC and independent immune hemolytic anemia, possibly Evans syndrome, that are likely related to oxaliplatin infusion. Bevacizumab cannot be completely ruled out as the cause of DIC in this patient, although there is far less evidence that bevacizumab can induce the hematological events described in this case report, the only evidence being a case series of renal TMA associated with vascular endothelial growth factor inhibition.…”
Section: Discussionmentioning
confidence: 87%
“…11,12 To our knowledge, there is only 1 other case report of oxaliplatin-induced DIC published in the medical literature, and the postulated mechanism of DIC in that patient was oxaliplatininduced fibrinolysis. 15 In our patient, DIC was clearly associated with acute hemolysis, and the presence of hemoglobinuria indicated a component of intravascular hemolysis. Thus, we postulate that acute intravascular hemolysis caused by reactive oxaliplatindependent autoantibodies was the initial triggering event and that this was complicated by DIC.…”
Section: Discussionmentioning
confidence: 94%
“…There are several other case reports showing associations between oxaliplatin and hematologic abnormalities such as immune-mediated hemolytic anemia [5,6], ITP [4,5], and thrombotic thrombocytopenic purpura [7]. However, there are only 3 case reports to date suggesting an association between oxaliplatin and DIC, all described in cases of metastatic colon cancer [9,10,11]. …”
Section: Discussionmentioning
confidence: 99%
“…This first published case reported was identified by hematuria a day after FOLFOX administration in a 66-year-old woman with metastatic colon cancer [9]. This patient had experienced oxaliplatin hypersensitivity without DIC several years previously, leading to discontinuation of oxaliplatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation